Optimizing anti-bullying programs on inclusive learning atmosphere in integrated islamic elementary school - Alfi Muhimmah, Hitta; Sukartiningsih, Wahyu; Dwi Wicaksono, Vicky; Hisman, Syariffanor binti; Mawaddah, Nurhayati (EduStream: Jurnal Pendidikan Dasar, 2025)
This study aims to examine the implementation of the anti-bullying program at the Integrated Islamic Elementary School (SDIT) At-Taqwa Surabaya in creating an inclusive learning atmosphere. This research employed a descriptive qualitative method with a case study design, using data collection techniques such as in-depth interviews, field observations, and document analysis. The findings show that a combination of preventive, collaborative, and supportive strategies is effective in building a safe, inclusive school environment and fostering students' holistic character development. This effectiveness is supported by systematic approaches such as daily pledges, early-year assessments, a house system, and the integration of religious values into the learning process, which help establish a positive school culture and strengthen peer relationships. Mandatory extracurricular programs and active parental involvement through parenting activities and the E-Bukpeng application further enhance bullying prevention efforts. Bullying cases are addressed in stages using a restorative approach, supported by sharing sessions and home visits to aid students' emotional recovery. The study concludes that optimizing anti-bullying programs based on religious values and family participation has proven effective in fostering a more positive and inclusive learning climate in Islamic elementary schools.